Differences in Students' Perceptions of the Community of Inquiry in a Blended Synchronous Delivery Mode - Anne-Marie Lafortune; Sawsen Lakhal (The Canadian Network for Innovation in Education (CNIE), 2020)
As more post-secondary institutions are turning to non-face-to-face course delivery modes to cater to the emerging needs of the student population, we have yet to find out whether students attending both at a distance and face-to-face have access to equal learning opportunities. A research was conducted in the nursing program taught in the blended synchronous delivery mode at the Cégep de la Gaspésie et des Îles over the winter 2017 semester. Using the Community of Inquiry framework and questionnaire elaborated by Garrison et al. (2000) and later revised by Shea and Bidjerano (2010), face-to-face (n=20) and at-a-distance (n=25) students' perceptions of the four Community of Inquiry presences (teaching, social, cognitive and learner) were measured and compared. Results of the overall presences comparison reveal that face-to-face participants perceived a stronger teaching presence than students attending from a satellite site, while the distinctive elements of each presence reveal significant difference between students' perceptions of the teaching, cognitive and learner presences. Additionally, students' comments provide rich qualitative data that explain the quantitative results obtained.